Dislocating Modernity : Two Projects by Hannes Meyer in Mexico - Lazo, Pablo (AA Files, 2002)
Colonia obrera en Lomas de Becerra, México D.F. 1942 -- Corpus Christi Block frente al monumento de Juárez en el centro de Alameda, México, 1947